2002
DOI: 10.1111/1468-5957.00460
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Ownership Structure and the Informativeness of Earnings

Abstract: This study extends prior studies by examining how managerial ownership and external unrelated blockholdings affect the informativeness of earnings. The results are in contrast to prior studies. A non-linear relation exists between managerial ownership and earnings informativeness. Earnings informativeness increases with managerial ownership at low levels but not at higher levels of managerial ownership where the entrenchment effect sets in. Consistent with the role of large shareholder monitoring, the evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 24 publications
10
151
1
10
Order By: Relevance
“…Our result is in line with those obtained by Machuga and Teitel (2009) with a sample of Mexican firms, who show that firms with less internal ownership show a greater earnings quality compared to those that do not have managerial ownership, i.e., shows less manipulative practices by managers, because of the implementation of good CG practices contained in Codes of Best Practices. Likewise, other studies such as Morck et al (1988) in Canada, Wartfield et al (1995) in the US, Yeo et al (2002) in Singapore and Sanchez-Ballesta and Garcia-Meca (2007) in Spain, also point out that the informativeness of accounting results increases with low levels of internal ownership, while for a high levels, the internal ownership is not sufficient as a mechanism of interest alignment.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Our result is in line with those obtained by Machuga and Teitel (2009) with a sample of Mexican firms, who show that firms with less internal ownership show a greater earnings quality compared to those that do not have managerial ownership, i.e., shows less manipulative practices by managers, because of the implementation of good CG practices contained in Codes of Best Practices. Likewise, other studies such as Morck et al (1988) in Canada, Wartfield et al (1995) in the US, Yeo et al (2002) in Singapore and Sanchez-Ballesta and Garcia-Meca (2007) in Spain, also point out that the informativeness of accounting results increases with low levels of internal ownership, while for a high levels, the internal ownership is not sufficient as a mechanism of interest alignment.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, since previous studies have found non-linearities which support both the convergence-of-interests and the entrenchment hypotheses in different ownership intervals (Morck et al 1988;Yeo et al 2002), we examine the possible non-linearities in the relation between insider ownership and discretionary accruals. In Table 5, model (12), we test the non linear effect of insider ownership (Int_OWN and Int_OWN2) on earnings management along with the other governance and control variables.…”
Section: Non-linear Relationsmentioning
confidence: 97%
See 3 more Smart Citations